2014
DOI: 10.1159/000360701
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis in Gulf War Era Veterans. 2. Military Deployment and Risk of Multiple Sclerosis in the First Gulf War

Abstract: Background: Concern has been raised that US veterans of the 1990-1991 Gulf War (GW1) may be at increased risk to develop neurologic disease. Methods: An incident cohort of multiple sclerosis (MS) and other demyelinating disease (ODD) was assembled from the US military comprising the Gulf War era (1990-2007). Cases of MS and ODD meeting standard diagnostic criteria were matched to a database of all active duty personnel from the Department of Defense. Relative risk (RR) estimates for MS and all demyelinating di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 84 publications
0
2
1
Order By: Relevance
“…By contrast however, a previous study in this setting showed that being in the country during the first Gulf War was significantly associated with increased odds of being a MS case than a control [ 28 ]. The finding of this study is also in contrast to the results of the previous studies based on the data from the United States veterans of World War II, Korean War [ 23 , 53 ] and a postwar epidemic in Iceland [ 21 ], which, together showed somewhat elevated MS risk in this subpopulation relative to the general population of the United States [ 25 , 54 ]. Furthermore, historically, it was claimed that the invasion and five-year occupation of Faroe Islands by British troops during the World War II introduced a widespread, specific, persistent (but unknown) and probably mild asymptomatic infection, as only one in 500 exposed individuals were clinically affected with primary MS [ 55 ].…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast however, a previous study in this setting showed that being in the country during the first Gulf War was significantly associated with increased odds of being a MS case than a control [ 28 ]. The finding of this study is also in contrast to the results of the previous studies based on the data from the United States veterans of World War II, Korean War [ 23 , 53 ] and a postwar epidemic in Iceland [ 21 ], which, together showed somewhat elevated MS risk in this subpopulation relative to the general population of the United States [ 25 , 54 ]. Furthermore, historically, it was claimed that the invasion and five-year occupation of Faroe Islands by British troops during the World War II introduced a widespread, specific, persistent (but unknown) and probably mild asymptomatic infection, as only one in 500 exposed individuals were clinically affected with primary MS [ 55 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A study of MS in veterans who served in the military between 1990 and 2007 and had applied for disability compensation identified increased MS rates in women, African Americans, and Army veterans compared to other groups but did not focus specifically on deployed veterans of the 1991 GW ( Wallin et al, 2012 ). A later report indicated that rates of MS were not significantly different between GW veterans and nondeployed veterans in this convenience cohort ( Wallin et al, 2014 ). Neither mortality data nor the number of veterans seeking disability benefits for MS provides a valid indication of whether GW veterans have been affected by excess rates of MS or most other neurological disorders since the war.…”
Section: The Epidemiology Of Gwimentioning
confidence: 59%
“…Other racial/ethnic minorities, including blacks, Hispanics and Asians, are also at risk of developing MS, although reported to have lower incidence rates in the United States [6, 7]. All-cause mortality has been reported to be significantly higher in people with MS compared to the general population with an estimated shorten life expectancy of 6–7 years [3, 8-11].…”
Section: Introductionmentioning
confidence: 99%